Early Detection of Ototoxicity Using 1/6th-Octave Steps - Fausti, Stephen A.; Helt, Wendy J.; Phillips, David S.; Gordon, Jane S.; Bratt, Gene W.; Sugiura, Karen M.; Noffsinger, Douglas (Journal of the American Academy of Audiology, 2003)
The National Center for Rehabilitative Auditory Research has developed a protocol to provide early identification of ototoxicity for patients receiving ototoxic medications. The initial work involved patients with relatively good high-frequency hearing and resulted in the use of an individualized, sensitive frequency range separated by 1/16th-octave intervals. This protocol tested puretone frequencies at 1/6th-octave steps above 9 kHz, but only conventional audiometric frequencies were tested below 9 kHz. More recently, the testing protocol was expanded to include 1/6th-octave testing below 9 kHz. The primary question of interest was to determine whether adding 1/16th-octave test frequencies below 9 kHz would increase the ototoxicity detection rate for patients with poorer hearing. Results indicated 76 of the 210 (36.2%) ears that demonstrated initial ototoxic hearing change would have been missed or detected later if only conventional frequency testing was conducted. Therefore, for individuals with poorer hearing, expanding the use of the 1/16th-octave test protocol provides earlier identification of ototoxicity.
Keywords: Early detection; hearing loss; individualized sensitive frequency range; ototoxicity; 1/6th-octave steps